FACTORS AFFECTING OIL CONTENT IN SOYBEAN SEEDS - Sobirova Mohinur Zokirjon qizi (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: Oil content is a critical quality parameter in soybean (Glycine max L.), influencing both its economic value and suitability for food and industrial uses. This study reviews and analyzes the major factors that affect oil accumulation in soybean seeds, including genetic variation, environmental conditions (temperature, moisture, sunlight), agronomic practices, and nutrient availability. Experimental observations and literature findings indicate that optimal fertilization, irrigation timing, and selection of high-oil-yielding cultivars can significantly increase oil content. Additionally, heat and drought stress during the seed-filling stage were found to negatively impact oil synthesis. Understanding these factors is essential for developing targeted strategies to enhance oil yield and overall crop quality in soybean production systems.